Conscientiousness and English Language Performance amidst the COVID-19 Pandemic: Mediation of Self-regulated Learning - Bourrouk, Khalid (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
Conscientiousness and self-regulated learning have been shown to directly impact students’ academic performance; however, whether or not such impact persists in the COVID-19 pandemic era requires further examination. Thus, this study aimed to investigate the association between conscientiousness, self-regulated learning and students' English language performance and examine the mediating effect of self-regulated learning in the relationship between conscientiousness and English language performance during the COVID-19 pandemic. By employing non-probability snowball sampling, 138 first and second-year undergraduate students enrolled at the University of Sidi Mohamed Ben Abdellah, Fez, Morocco, participated in the study by completing a 21-item questionnaire. Using linear regression, the study found a statistically significant relationship between conscientiousness and self-regulated learning [F (1, 136) = 77.41, p < .001, R2 = .37]. Next, a multiple regression analysis was conducted and revealed that while self-regulated learning significantly predicted English language final grades (β = .41, p < .001), conscientiousness was not a significant predictor (β = .14, p > .001). A Sobel test was performed and showed that self-regulated learning was able to mediate the relationship between conscientiousness and English language grades (p < .001). The study concludes that although conscientious students are driven by their diligent work habits, those who lacked effective self-regulated learning strategies received lower grades in their English language class. Hence, educators must concentrate much of their efforts on helping students develop efficient self-instruction, self-monitoring, and self-evaluation techniques that can propel learners into achieving their academic goals.